REDUKSI LENDUTAN PCI GIRDER DENGAN PEMASANGAN DIAFRAGMA - Aprilia Rossa Ariesta; Andi Indianto; Erlina Yanuarini (Prokons: Jurnal Teknik Sipil, 2022)
AbstractKeramasan Bridge 2 is a bridge with an age of more than 30 years, so it is necessary to review its feasibility and serviceability. Based on the loading test results, it is stated that the deflection on the girder exceeds the permissible deflection. Based on this, it is necessary to strengthen the upper structure. The strengthening of the upper structure is carried out by installing a diaphragm between the girders. The diaphragm is an angled steel profile of 100 mm x 100 mm with a thickness of 10 mm.To determine the number and position of diaphragms, two alternatives were analyzed. The first alternative is to add three diaphragms at 1/4, 1/2, and 3/4 span. In the first alternative, the deflection value is 26.9754 mm. In the second alternative, the diaphragm is installed every 3 meters distance. The addition of the diaphragm produces a deflection of 27.1634 mm. The results of the analysis indicate that with the addition of a diaphragm, there is a reduction in deflection. In the first and second alternatives, a deflection that meets the permissible deflection is produced (31.375 mm). Considering the safety factor, the first alternative is used because adding three diaphragms affords the smallest deflection (26.9754 mm).Keywords: Deflections, Diaphragm, Strength, Bridge Upper Structure